Physician-patient deaf relations: a bibliographic review of the last 10 years (Research, Society and Development, 2020)
This article aims to analyze the doctor-deaf patient relationship and their communication barriers in the last decade and to seek solutions to improve this failure. it is a bibliographic review of scientific literature, which an electronic data survey was carried out in the Biblioteca Virtual em Saúde (BVS) and SciELO databases. The research was carried out using the keywords obtained through Descritores em Ciências da Saúde (DeCS) and filters in Portuguese, in English and between the period 2010 to 2020 and data from the Instituto Brasileiro de Geografia e Estatística (IBGE) and the Ministry of Health with a non-systematic way. It was analyzed that the little knowledge about Libras, combined with an inadequate infrastructure for the reception of deaf patients, collaborates to the majority of medical professionals do not offer quality assistance to them, and it is common to hire interpreters by hospitals and care units for a better communicative approach. However, even if the interpreters have knowledge about Libras, the respect for patient confidentiality and medical ethical issues are not imposed to them. Thus, due to the low stimulation during academic training, there are still few professionals who communicate properly with deaf patients. The adaptation of hospital infrastructures and the teaching of Libras during the training of these professionals can help to overcome the communication barriers between the doctor and the deaf patient and, consequently, improve care.